PERAWATAN GIGI TIRUAN SEBAGIAN LEPASAN TERHADAP GANGGUAN ESTETIK, FONETIK, MASTIKASI DISERTAI GANGGUAN TEMPOROMANDIBULAR DISORDER (CASE RESPORT) - Fidelia, Marvella; Naliani, Silvia; Wijaya, Fatta; Dwiarie, Theodora Adhisty; Sumantri, Dominica Dian Saraswati (Universitas Baiturrahmah, 2025)
Introduction: Tooth loss leads to several undesirable conditions, including the migration of adjacent teeth, tooth rotation, extrusion of opposing teeth, temporomandibular joint disorders, excessive load on supporting tissues, aesthetic dysfunction, and impaired speech function. Case and Management: A 47-year-old male presented with a complaint of missing teeth in both his upper and lower jaws, and he sought to have removable dentures fabricated. The patient is having trouble speaking, particularly with certain words, temporomandibular joint sounds and lacks confidence due to the loss of their front teeth. He is also having trouble eating becauseof difficulty chewing. Management for this patient is by making an acrylic removable partial denture to improve occlusion. Aesthetic and functional improvements in the anterior region of the teeth can be achieved with the use of dentures, including removable partial dentures. The temporomandibular joint and occlusion are functional units, so disturbances in occlusion will affect the mechanism of the jaw joint. Functional disorders of the TMJ include pain and temporomandibular joint dysfunction, such as joint sounds (clicking). Conclusion: Patients experienced a significant difference in chewing function between not wearing dentures and using removable partial dentures (RPD), with a decrease in joint sounds and pain. The success of the treatment is supported by proper design planning and correct treatment procedures. Keywords: masticatory disturbance, removable partial denture, temporomandibular disorder, tooth loss